Determinants of Deposit-Insurance Adoption and Design - Demirguc-Kunt, Asli; Kane, Edward J.; Laeven, Luc (2012)
This paper identifies factors that influence decisions about a country's financial safety net, using a comprehensive data set covering 180 countries during the 1960-2003 period. Our analysis focuses on how private interest-group pressures, outside influences, and political-institutional factors affect deposit-insurance adoption and design. Controlling for macroeconomic shocks, quality of bank regulations, and institutional development, we find that both private and public interests, as well as outside pressure to emulate developed-country regulatory schemes, can explain the timing of adoption decisions and the rigor of loss-control arrangements. Controlling for other factors, political systems that facilitate intersectoral power sharing dispose a country toward design features that accommodate risk-shifting by banks.